2005
DOI: 10.3189/172756505781829151
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic variation within polar firn caused by differential accumulation and ice flow: interpretation of a 400 MHz short-pulse radar profile from West Antarctica

Abstract: We investigate causes of the stratigraphic variation revealed in a 177 km, 400 MHz shortpulse radar profile of firn from West Antarctica. The profile covers 56 m depth, and its direction was close to those of the ice flow and mean wind. The average, near-surface accumulation rates calculated from the time delays of one radar horizon consistently show minima on leeward slopes and maxima on windward slopes, confirming an earlier study based on stake observations. The stratigraphic variation includes up to 30 m d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 28 publications
6
75
0
Order By: Relevance
“…7 is a wellknown feature caused by spatial variations in accumulation rates (see e.g. Arcone et al, 2005b). To conclude, the undulations we observe would be the result of accumulation variations caused by interactions between katabatic wind and local topography.…”
Section: Undulating Structuresmentioning
confidence: 86%
See 2 more Smart Citations
“…7 is a wellknown feature caused by spatial variations in accumulation rates (see e.g. Arcone et al, 2005b). To conclude, the undulations we observe would be the result of accumulation variations caused by interactions between katabatic wind and local topography.…”
Section: Undulating Structuresmentioning
confidence: 86%
“…To conclude, the undulations we observe would be the result of accumulation variations caused by interactions between katabatic wind and local topography. These processes are described in Arcone et al (2005b).…”
Section: Undulating Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed by Arcone et al (2005), the apparent dune drift velocity observed in the GPR images is a combination of the real dune velocity and the ice movement, and the real dune velocity is higher than the observed one. According to (Richter et al, 2013), ice flow velocities in this region do not exceed 2 m yr −1 , so the real dune drift velocity could be up to 6.6 m yr −1 .…”
Section: Megadune Driftmentioning
confidence: 78%
“…Reflections seen in radar recordings can sometimes be associated with distinct accumulation or melt events, or depth hoar layers (Eisen et al, 2004;Arcone et al, 2005;Helm et al, 2007;Dunse et al, 2008). Analysis of internal layers in ice and snow with commercial GPR systems for estimating accumulation has been demonstrated by Arcone et al (2004), Dunse et al (2008), and Heilig et al (2010), amongst others.…”
Section: Introductionmentioning
confidence: 99%